Mammal abundance and diversity in oil palm cultivations in Peninsular Malaysia - Ibrahim, Nor Laili (2012)
Currently, oil palm is one of the world’s leading crops with rapidly increasing demand but it lead to conservation issues like tropical deforestation and biodiversity. As such values are likely to be one of the major conservation issues across the globe. Therefore, conservation efforts for these threatened and endangered species, especially terrestrial mammal often suffer due to a lack of information on species requirements or their distribution. Nowadays, terrestrial mammals are not only confined to nature reserves and protected area, but also becoming widespread in other land uses as well as within oil palm landscape. managed to record a total of 18,052 individual animals from 40 species including seven most endangered species. Among them, the primate species was the most commonly registered mammals, with the Malayan Sun Bear being frequently present, thus showing significantly higher numbers in smallholdings than in plantation estates (p < 0.05) at standing age of oil palm more than 20 years. Oil palm management plays an important role in the influence of mammal diversity and abundance. It is noticed that the smallholdings were planted with different crops. As a result, this specific practice may have directly or indirectly improved the complexity of plant richness and habitat which benefited some mammal species. In conclusion, this study has been able to demonstrate that most of the oil palm areas can support some native mammals, if hunting and conflict in human-wildlife problem can be overcomes by plantation stakeholders. Apart from forest conservation, the studies have also recommended that the oil palm-dominated areas be managed more as an off-reserve strategy in order to protect the mammal diversity.